2020
DOI: 10.1002/adfm.201910538
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of Dual‐Phase Lithium Storage in a Porous Carbon Host for Lithium‐Metal Anode

Abstract: Lithium (Li) metal is regarded as the most attractive anode material for high-energy Li batteries, but it faces unavoidable challenges-uncontrollable dendritic growth of Li and severe volume changes during Li plating and stripping. Herein, a porous carbon framework (PCF) derived from a metal-organic framework (MOF) is proposed as a dual-phase Li storage material that enables efficient and reversible Li storage via lithiation and metallization processes. Li is electrochemically stored in the PCF upon charging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 53 publications
1
60
0
Order By: Relevance
“…A stable and conformal SEI is formed to isolate the Li metal and electrolyte solvents, avoiding deleterious side reactions. [ 132–140 ]…”
Section: Porous Materials As LI Hostsmentioning
confidence: 99%
See 1 more Smart Citation
“…A stable and conformal SEI is formed to isolate the Li metal and electrolyte solvents, avoiding deleterious side reactions. [ 132–140 ]…”
Section: Porous Materials As LI Hostsmentioning
confidence: 99%
“…A stable and conformal SEI is formed to isolate the Li metal and electrolyte solvents, avoiding deleterious side reactions. [132][133][134][135][136][137][138][139][140] In 2014, Zheng et al designed a flexible, crosslinking, porous, hollow carbon sphere to induce homogenous Li deposition. [141] The hollow carbon nanospheres were coated on the Cu substrate by the chemical process.…”
Section: Porous Materials As LI Hostsmentioning
confidence: 99%
“…Based on above aspects, we have reported that the physical properties of nanoporous zeolitic imidazolate framework (ZIF)-derived carbons can be controlled by different ratios of zinc (Zn) to cobalt (Co)-ion metallic precursors [19][20][21]. This approach was designed to achieve tailored ZIF-derived carbons with different pore volumes, pore sizes, surface areas, and even degrees of graphitization.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Graphite is the most broadly used and commercialized anode material for LIBs; however, owing to its limited theoretical capacity (372 mAh/g), it cannot fully meet the demand for high capacity. [3][4][5] Silicon has recently emerged as a promising alternative to graphite as an anode for LIBs due to its exceptionally high theoretical capacity (Li 15 Si 4 , 3580 mA h g −1 ). 6,7 However, the practical utilization of silicon anode is hindered by a severe volume change of up to 300% during cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial effort has been exerted to identify a new anode material with a high capacity, long cycle performance, high power density, and high coulombic efficiency for lithium‐ion batteries (LIBs) 1,2 . Graphite is the most broadly used and commercialized anode material for LIBs; however, owing to its limited theoretical capacity (372 mAh/g), it cannot fully meet the demand for high capacity 3‐5 …”
Section: Introductionmentioning
confidence: 99%